Adolescents' mutual acculturation attitudes and their association with national self-identification in three Swiss cantons - Sidler, Petra (Frontiers in Sociology, 2023)
Acculturation is a mutual process, meaning that members of minority as well as majority groups acculturate and thus experience cultural and psychological changes when having intercultural contact. This study assessed mutual acculturation attitudes in the school context through a four-dimensional measurement examining attitudes toward (1) migration background students’ heritage culture maintenance and their (2) dominant culture adoption, (3) majority students’ intercultural knowledge acquisition, and (4) schools’ intercultural contact endorsement. Acculturation attitudes are commonly analyzed through minority and majority perspectives; however, the ways in which researchers categorize group members can differ significantly from how those members self-identify. This matters particularly for adolescents because they explore group identities and belongings. So far, adolescents’ mutual acculturation attitudes have not been studied in relation to national self-identification measures. The current study addressed this research gap by analyzing mutual acculturation attitudes in relation to how strongly adolescents self-identify as (1) being Swiss, (2) having a migration background, and (3) the interaction of the two. The sample consisted of 319 adolescents in public secondary schools in three German-speaking cantons in Switzerland (45% female, Mage = 13.60 years, range 12–16). Latent profile analyses resulted in three distinct mutual acculturation profiles. The first is a mutual integration profile (n = 147, 46%), where minority and majority adolescents and schools are expected to integrate. The second is a multiculturalism profile (n = 137, 43%), with slightly lower expectations in all dimensions. The third is a cultural distancing profile (n = 33, 10%), which places particularly low expectations on majority adolescents and schools. Through an analysis of variance and a multiple logistic regression, those in the cultural distancing profile were found to identify significantly stronger as not having a migration background compared to those in the mutual integration profile. Thus, students having separation expectations toward minority students and non-involvement expectations toward schools and majority students are more likely to self-identify as not having a migration background than students having mutual integration expectations.